First Nations Popular Music in Canada: Musical Meaning and the Politics of Identity - Scales, Christopher (Canadian University Music Review / Revue de musique des universités canadiennes, 1999)
The musics of First Nations popular musicians "Wapistan" Lawrence Martin and the Innu group Kashtin are examined as polysemic signs whose meaning is mediated both socially and politically in the ongoing construction of First Nations socio-cultural identity. Musical meanings on individual, local, national, and international levels are dependent on the socio-political positioning of both the performers and the audience. Because socio-political positions are themselves fluid, political meanings are, as well, in constant flux. As a polysemic sign, First Nations popular music is a locus for these various meanings and a site for the construction and deconstruction of political discourse.